Pengaruh Biaya Lingkungan dan Kinerja Lingkungan Terhadap Nilai Perusahaan - Bella Anggriani; Usep Syaipudin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research is motivated by increasing public attention to environmental issues, especially in the manufacturing sector which has great potential to pollute the environment. This study aims to analyze the effect of environmental costs and environmental performance on the value of manufacturing companies listed on the IDX and participating in the KLHK PROPER program in the 2020-2023 period. This quantitative research uses secondary data from the company’s annual report, PROPER report, and IDX. The sample was determined by purposive sampling and consisted of 30 companies. The independent variables are environmental costs and environmental performance, with firm value as the dependent variable measured through Tobin’s Q ratio. Control variables include profitability, firm size, and firm age. The data analysis technique uses the SPSS version 25 tool with descriptive statistical tests, classical assumption tests, and hypothesis testing. The results showed that environmental performance has a positive and significant effect on firm value, while environmental costs have no significant effect. This means that firm value is more influenced by environmental performance than the amount of costs incurred for these activities.